Avaliação hidrogeológica do sistema aquífero Parecis na cidade de Sinop–MT e seu entorno - Lussi, Cassiana (2013)
The area of this work involves the Sinop city region in central northern state of Mato Grosso, where the main is groundwater reservoir. The public supply and economic activities rely solely the groundwaters and their knowledge is limited. In this scenario this study general aims to hydrogeological characterization the Parecis Aquifer System in the city of Sinop – MT and its surrounding. Was estimated the thickness and depth to top of the geologic units that occur in the area, was determined the hydrodynamic parameters of the Utiariti and Salto das Nuvens aquifer and estimated reserves of groundwater Parecis Aquifer System (PAS). To estimate the thickness and depth to the top has been using the technique of vertical electrical sounding (VES), with maximum aperture of AB/2 of 1.000 m. There were twenty SEV, the results show that the soil cover has a thickness range of 1,6 m to 6,0 m. The Utiariti formation has an average thickness of 76m and the average depth of 4,3 m. The Salto das Nuvens formation have an average thickness of 195m and depth of 81m. The hydrodynamic parameters estimated for Utiariti aquifer are: transmissivity of 2,65x10-2 m2/s, hydraulic conductivity of 3,49 x 10-4 m and storage coefficient of 3,54x10-3 . The specific capacity of the wells to vary the PAS ranges from 1,06m2/h to 4,17m2/h. The groundwater reserves were estimated to PAS: permanent of 226,9x108m3, regulator of 18,58x107m3/year, total of 228,74x108m3 and exploitable of 4,6x107m3/year. The potentiality of the PAS is 32,3x107m3/year. These data show that PAS is a good aquifer system capable of supplying large exploitation of water. The results of this study contribute to a better hydrogeological knowledge of the area, for elaboration management plan, for groundwater vulnerability assessment and for the risk of groundwater contamination.